2011
DOI: 10.1002/dac.1261
|View full text |Cite
|
Sign up to set email alerts
|

A framework for fiber delay‐line buffers in packet‐based asynchronous multifiber optical networks (PAMFONET)

Abstract: SUMMARY A major challenge in packet‐based optical networks is packet contention, which occurs when two or more packets are heading to the same output at the same time. To resolve contention in the optical domain, a fundamental approach is fiber delay‐line (FDL) buffering, in which packets can be delayed for a fixed amount of time. In the literature, the performance of FDL buffering has been studied extensively. However, most existing works are based on an assumption that there is only one fiber per link in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 26 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…Shared buffer and dedicated buffer exist a trade‐off between them in terms of cost and complexity implementation, which motivates us to do the following comparison. Zhang proposed a working framework for optical buffers in a packet‐based optical network, which is divided into two main types: shared and dedicated buffer architectures. Tafani et al presented a cost minimization framework for OBS network with shared‐per‐node optical buffers.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…Shared buffer and dedicated buffer exist a trade‐off between them in terms of cost and complexity implementation, which motivates us to do the following comparison. Zhang proposed a working framework for optical buffers in a packet‐based optical network, which is divided into two main types: shared and dedicated buffer architectures. Tafani et al presented a cost minimization framework for OBS network with shared‐per‐node optical buffers.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…1) has an optical buffer in which N + 1 FDLs are available to schedule incoming packets corresponding to the architecture in [4] named "dedicated FDL buffers per fiber". The lengths of the FDLs are consecutive multiples of a basic value D called the granularity.…”
Section: A Assumptionsmentioning
confidence: 99%
“…Because of the lack of mature optical memory, contention reduces OBS performance remark- ably. To enhance the performance of OBS and make it more competitive, many methods have been proposed such fiber delay lines [6], deflection routing [7], wavelength conversion [8], and burst segmentation [9], A review of routing strategies as means to reduce contention in OBS can be found in [10]. Furthermore, different OBS architectures have been proposed to improve its performance [11].…”
Section: Introductionmentioning
confidence: 99%